Scaling up of tigershrimp (Penaeus monodon) production in brackishwater pond under diversified cropping regimes - Washim, Mizanur Rahman; Rahman, Syed Lutfor; Rubel, AKM Shafiqul Alam (Asian Journal of Medical and Biological Research, 2018)
To develop a scientific and affordable shrimp farming system for marginal to medium farmers with low inputs and higher returns by scaling up of production per unit area, shrimp culture was practiced with 3, 5 and 7/m2 stocking densities for the period of 60 days as short cycle and 120 days as long cycle. All the hydrographical parameters were found congenial in different treatments except dissolved oxygen (DO) in case of higher stocking density and long culture pattern. However, the specific growth rate (SGR) was optimal in both culture cycle but increased sharply in first 3-4 weeks of grow out period. Distinct survival rate were found in different treatment which was ranged from 86.39 to 90.96% but did not show significant difference (P>0.05%) among the treatments of short and long culture cycle. Total yield was ranged from 990 kg/ha to 1998 kg/ha for short cycled double and 1012 kg/ha to 2032 kg/ha for single cropping pattern. Highest production was obtained under the stocking densities of 7/m2although the average production showed significant difference (P<0.05%) among the treatments of both culture patterns. The food conversion ratio (FCR) value seems similar for all cropping patterns and ranged between 1.15 and 1.57. Except stocking density of 7/m2 at short cycle culture, net benefit were significantly (P>0.05%) higher in long cycle crop than that of aggregate of two short cycle crops. But benefit cost ratio (BCR) in short culture cycle is significantly (P>0.05%) higher than that of long culture (120 days) which indicates higher net benefit as well as positive feasibility of short culture system. Considering the infrastructural facilities in farm level and resource capability, this shrimp farming technology would be appropriate to boost up the production and income particularly for marginal to medium farmers. Asian J. Med. Biol. Res. March 2018, 4(1): 27-35